2018
DOI: 10.1111/1365-2745.13016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of increased intraspecific competitive ability following introduction: The importance of relatedness among genotypes

Abstract: A long‐standing explanation for invasion success is that invasive plants could evolve to be more competitive following introduction. This evolution of increased competitive ability (EICA) hypothesis, however, has seldom been tested with regard to intraspecific competition. Given that plants can display different responses to related and unrelated conspecifics, the evolution of intraspecific competitive ability might be specific to genotypes of different relatedness. Here, we grew five native (South American) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
0
26
1
1
Order By: Relevance
“…Because invasive plants in the introduced range are likely to have neighbors of closely related kin because of their reduced genetic diversity following introduction, they might evolve the ability of kin recognition and a reduced competitive response to kin. For instance, Zhang et al (2019) showed that introduced Alternanthera philoxeroides produced more branches when competing with kin compared to when competing with unrelated genotypes, which consequently increased vegetative reproduction by stem fragmentation. Reduced competitive response to kin potentially increases the fitness of invasive species in the initial stage of invasion, and consequently promotes establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Because invasive plants in the introduced range are likely to have neighbors of closely related kin because of their reduced genetic diversity following introduction, they might evolve the ability of kin recognition and a reduced competitive response to kin. For instance, Zhang et al (2019) showed that introduced Alternanthera philoxeroides produced more branches when competing with kin compared to when competing with unrelated genotypes, which consequently increased vegetative reproduction by stem fragmentation. Reduced competitive response to kin potentially increases the fitness of invasive species in the initial stage of invasion, and consequently promotes establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of A. philoxeroides to date have focused on differences between plants from the native and invaded range and explored development and performance of the biocontrol agent or plant defensive responses rather than biomass response (equivalent to successful control) of the plants to feeding (Liu et al 2018;Pan et al 2013;Zhang et al 2019). It will therefore be valuable to determine how effective the currently available biological control agents will be on the introduced haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Butomus umbellatus establishment and spread in North American aquatic habitats has generated negative ecological and economic impacts, leading to increased interest in predicting invasiveness, potential distribution (Banerjee et al, in prep), and development of effective management tools for the species [59,70,71]. However, research on B. umbellatus management has largely failed to take into account genetic variation and the implications of differences in ploidy in the invaded range (but see [72][73][74][75][76][77][78][79][80]. However, it is rare that genetic identity of an invader is paired with plasticity to environmental variables and interspecific competition in order to assess invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Griseb. (Amaranthaceae) (competition, herbivory, water level) [72][73][74][75][76][77][78][79][80]. However, it is rare that genetic identity of an invader is paired with plasticity to environmental variables and interspecific competition in order to assess invasive potential.…”
Section: Discussionmentioning
confidence: 99%